(untitled) (Proceedings of the Mongolian Academy of Sciences, 2019)
Central Asia is one of the seismically most active regions in the world. Its complex seismicity is due to the collision of the Eurasian and Indian plates, which has resulted in some of the world’s largest intra-plate events over history. The region is dominated by reverse faulting over strike slip and normal faulting events.The GSHAP project, aiming at hazard assessment on a global scale, indicates that the territory of Bayankhongor aimag, Mongolia, in Central Asia is characterized by maximum bedrock peak ground accelerations for 10% probability of exceedance in 50 years as medium as in range of 80 to 160cm/s2. In this study, which has been carried out within the framework of the project “Seismic microzoning map of center of 12 aimags, Mongolia”, the area source model and different kernel approaches are used for a probabilistic seismic hazard assessment for the Mongolia. The seismic hazard is assessed considering shallow (depth <50 km) seismicity only and employs an updated (with respect to previous projects) earthquake catalogue for the region. The hazard maps, shown in terms of 10% probability of exceedance in 50 years, are derived by using the Open Deterministic and Probabilistic Seismic Hazard Assessment (ODPSHA), which is based on the Cornell methodology. The maximum hazard observed in the region reaches 93-98 cm/s2 , which in intensity corresponds to VII in MSK64 scale in the centre of Bayankhongor aimag for 475 years mean return period.